2005
DOI: 10.1209/epl/i2004-10420-2
|View full text |Cite
|
Sign up to set email alerts
|

The size distribution of Si nanoparticles prepared by pulsed-laser ablation in pure He, Ar or Ne gas

Abstract: Nanocrystalline silicon films were prepared by pulsed-laser ablation in high-purity He, Ar or Ne gas at room temperature under a deposition pressure of 10 Pa. The Raman and Xray diffraction spectra indicate that the films are nanocrystalline. Scanning electron microscopy images show that Ar or Ne gas, compared to He gas, yields smaller and more uniform-sized Si nanoparticles at the same deposition conditions, which is also confirmed by the blue-shifted and narrower peaks obtained in photoluminescence measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Si nanoparticles, being formed between target and substrate, are transported to the substrate and adsorbed on the substrate. In terms of the nucleation area model [7] , Si nanoparticles were formed in a certain range, called nucleation area. The nucleation was a process of gas phase in the PLD, it is depended on the temperature of Si atoms .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Si nanoparticles, being formed between target and substrate, are transported to the substrate and adsorbed on the substrate. In terms of the nucleation area model [7] , Si nanoparticles were formed in a certain range, called nucleation area. The nucleation was a process of gas phase in the PLD, it is depended on the temperature of Si atoms .…”
Section: Resultsmentioning
confidence: 99%
“…The experimental setup is similar to that used in the previous experiments [7] . Briefly, in pure Ar gas under ambient pressure of 10 Pa, a Lambda Physik XeCl excimer laser (wavelength 308 nm, pulse duration 15 ns, repetition rate 3 Hz)…”
Section: Description Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea can be extended to the nucleation and growth of nanoscale structures with other configurations in various preparation methods. To explain the experimental result that Ne gas induces the smallest and most uniform Si nanoparticles (np-Sis, i.e., Si nanograins, nanocrystals, nanoclusters or quantum dots) among He, Ar, and Ne, we proposed a qualitative model (Fu et al, 2005), which indicated that for ns-PLD, there are three regions, labeled "high energy region," "nucleation region" (NR), and "transporting region." The mean size and size-consistency of np-Sis depend on the width of NR where the nucleation and growth occur.…”
Section: Introductionmentioning
confidence: 99%